2022
DOI: 10.1038/s41556-022-00857-4
|View full text |Cite
|
Sign up to set email alerts
|

Gasdermin E mediates resistance of pancreatic adenocarcinoma to enzymatic digestion through a YBX1–mucin pathway

Abstract: Pancreatic ductal adenocarcinoma (PDAC) originates from normal pancreatic ducts where digestive juice is regularly produced. It remains unclear how PDAC can escape autodigestion by digestive enzymes. Here we show that human PDAC tumour cells use gasdermin E (GSDME), a pore-forming protein, to mediate digestive resistance. GSDME facilitates the tumour cells to express mucin 1 and mucin 13, which form a barrier to prevent chymotrypsin-mediated destruction. Inoculation of GSDME−/− PDAC cells results in subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…[28] This mucus-based physiological protection mechanism prompted us to hypothesize that PDAC cells use the same process to protect themselves from pancreatic enzymatic digestion. We indeed provide evidence that PDAC cells highly upregulate MUC1 and MUC13 expressions, concomitant with resistance to digestive enzymes, [29] while normal human pancreatic cells express much lower levels of MUC1 and MUC13 and lack resistance to these enzymes (Fig. 1B).…”
Section: Mucus Acts As An Armor Protecting From Digestive Enzymessupporting
confidence: 56%
See 2 more Smart Citations
“…[28] This mucus-based physiological protection mechanism prompted us to hypothesize that PDAC cells use the same process to protect themselves from pancreatic enzymatic digestion. We indeed provide evidence that PDAC cells highly upregulate MUC1 and MUC13 expressions, concomitant with resistance to digestive enzymes, [29] while normal human pancreatic cells express much lower levels of MUC1 and MUC13 and lack resistance to these enzymes (Fig. 1B).…”
Section: Mucus Acts As An Armor Protecting From Digestive Enzymessupporting
confidence: 56%
“…[25] Mucin-type O-glycosylation can maintain gastric homeostasis and protect it from chronic gastritis-associated cancer, [33,34] and a decreased mucus thickness with impaired O-glycosylation causes gastric illness in people. [35] Of note, the O-linked glycosylation of MUC1 and MUC13 has been widely observed in PDAC, colon cancer, and mammary carcinoma [29,36] and is associated with a poor prognosis in cancer patients. We demonstrate that O-linked glycosylation of MUC1 and MUC3 facilitates the resistance of PDAC cells to pancreatic enzymatic digestion.…”
Section: Mucus Acts As An Armor Protecting From Digestive Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…GSDMD can also translocate to the nucleus and act as a PARP-1 inhibitor to induce DNA damage and apoptosis in colorectal cancer cells ( 76 ). Furthermore, GSDME transports a transcriptional factor YBX1 into the nucleus, which increases mucin expression and promotes the formation of a mucus barrier that prevents chymotrypsin-mediated destruction of pancreatic ductal adenocarcinoma ( 77 ). Therefore, the effects of GSDM expressions on tumor growth may be determined by both the pyroptosis and non-pyroptotic functions, which sometimes have opposite impacts on tumorigenesis.…”
Section: The Cancer-associated Pyroptosis In Tumorsmentioning
confidence: 99%
“…For example, Han et al utilized metformin to disrupt the dense matrix by activating adenosine phosphate-activated kinase pathway, thereby promoting the penetration and therapeutic effect of the DDS [ Figure 1A ] [ 48 ] . Lv et al showed that PDAC cells utilized gasdermin E to mediate resistance to digestive juices in the pancreatic microenvironment [ 72 ] .…”
Section: Mechanisms Of Tumor Resistancementioning
confidence: 99%